2022
DOI: 10.1177/21925682221099470
|View full text |Cite
|
Sign up to set email alerts
|

How to Optimize Pedicle Screw Parameters for the Thoracic Spine? A Biomechanical and Finite Element Method Study

Abstract: Study Design Pedicle screw study. Objective The selection of pedicle screw parameters usually involves the surgeon’s analysis of preoperative CT imaging along with anatomical landmarks and tactile examination. However, there is minimal consensus on a standardized guideline for selection methods on pedicle screws. We aimed to determine the effects of thoracic screw diameter to pedicle width on pullout strength determined by cortical bone purchase. Methods Biomechanical study performed with human cadaveric thora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Mechanical tests and numerical simulations are commonly used biomechanical methods for determining screw anchoring ability ( Chao et al, 2008 ; Solitro et al, 2022 ). Although mechanical tests can directly reflect screw anchoring ability by directly recording the screw displacement values in each cycle, detailed stress distribution patterns, especially at the bone-screw interfaces, cannot be directly reflected by this method.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical tests and numerical simulations are commonly used biomechanical methods for determining screw anchoring ability ( Chao et al, 2008 ; Solitro et al, 2022 ). Although mechanical tests can directly reflect screw anchoring ability by directly recording the screw displacement values in each cycle, detailed stress distribution patterns, especially at the bone-screw interfaces, cannot be directly reflected by this method.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the uniformed screws were utilized in the construction of two models (6.5 mm for LSIF, 5.5 mm for TSEF). If each screw model were constructed based on the SD/PW ratio (screw diameter/pedicle width) as previously documented ( Solitro et al, 2019 ; Solitro et al, 2024 ), the model would more accurately reflect the variability in dimensions of the lumbar segments. In a study regarding the screw pullout load reported by Giovanni F. Solitro et al, given that the friction coefficient and shear stress are critical for screw pullout analysis, a layer surrounding the screw was modeled to include a failure for shear ata value of 1, and the bone-screw interface was modeled as surface-to-surface contact with a coefficient of friction of 2 ( Solitro et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…If each screw model were constructed based on the SD/PW ratio (screw diameter/pedicle width) as previously documented ( Solitro et al, 2019 ; Solitro et al, 2024 ), the model would more accurately reflect the variability in dimensions of the lumbar segments. In a study regarding the screw pullout load reported by Giovanni F. Solitro et al, given that the friction coefficient and shear stress are critical for screw pullout analysis, a layer surrounding the screw was modeled to include a failure for shear ata value of 1, and the bone-screw interface was modeled as surface-to-surface contact with a coefficient of friction of 2 ( Solitro et al, 2024 ). In the prsenting study, we focused on ROM of the lumbar spine and stresses on model elements in the TSEF and LSIF models, hence the bone-screw interface was defined as binding contact without modeling surrounding screws ( Xu et al, 2014b ).…”
Section: Discussionmentioning
confidence: 99%
“…As with most of the pilot studies, the current study has several limitations that we will overcome, extending the methodology proposed here on cadaveric specimens. We used bone surrogates, as is commonly done in the field of orthopedic biomechanics research when more than two configurations need to be tested to address a particular research question [ 37 , 38 , 39 ]. Beckmann et al used more than two configurations in order to determine which of the three tested fixation techniques, i.e., cement-only, screw- only, and combination of cement and screw, provided the most stable bond between the porous titanium acetabular component and augment [ 37 ].…”
Section: Discussionmentioning
confidence: 99%